Pharmaceutical Preparation of Amrita Guggulu and its Clinical Efficacy on Vatarakta (AYUSHDHARA, 2024)
This study scrabbles about into the pharmaceutical preparation of Amrita Guggulu, a traditional Ayurvedic formulation known for its therapeutic properties. The focus of the research is on assessing the clinical efficacy of Amrita Guggulu in managing Vatarakta, a condition characterized by vitiated Vata as well as Pitta and associated with inflammatory joint disorders. The pharmaceutical preparation involves meticulous formulation techniques, ensuring the quality and potency of the final product. Standardization parameters include the selection of authentic raw materials, adherence to traditional preparation methods and quality control measures. Clinical Trial Design: The clinical trial was designed as a randomized, double-blind study to assess the efficacy of Amrita Guggulu in patients diagnosed with Vatarakta. Participants were randomly assigned to either the treatment group receiving Amrita Guggulu group A or group B. A comprehensive clinical trial was conducted to evaluate the efficacy of Amrita Guggulu in patients diagnosed with Vatarakta. Key parameters such as joint pain, inflammation in joint, tenderness, burning sensation in affected area, skin rashes and tingling sensation were selected for the study. Overall improvement was assessed using standardized tools and patient-reported outcomes. Result: Preliminary findings indicate promising results, suggesting that Amrita Guggulu may play a significant role in alleviating symptoms associated with Vatarakta. The observed effects include a reduction in joint pain, improved joint function, and decreased inflammatory markers. Conclusion: This research contributes valuable insights into the pharmaceutical preparation of Amrita Guggulu and highlights its potential as an effective intervention for Vatarakta. On the basis of this clinical trial, we can say that S. Uric acid is not the confirmatory parameter for the decision of Vatarakta (gout). Further studies and long-term observations are recommended to solidify these findings and establish Amrita Guggulu as a viable therapeutic option in managing inflammatory joint disorders.